The Effects of Benson Relaxation Therapy in Exploratory Laparotomy Appendicitis: A Case Study - Yumna Lis Nur Fadhila; Yanuar Primanda; Suprianto Suprianto (Jurnal Kesehatan Saintika Meditory, 2025)
Appendicitis is inflammation of the vermiform appendix and is considered a common cause of abdominal diseases in low and middle-income countries, including Indonesia. In Indonesia, the incidence of appendicitis is highest compared to other cases of abdominal emergencies. Accurate diagnosis and appropriate surgical treatment significantly reduce the mortality and morbidity rate of this disease. Surgery will trigger stress reactions, both physiological and psychological, that can cause anxiety. Appendicitis also cause pain, which is felt both before surgery and as a post-surgery. Benson Relaxation Therapy can be effective in reducing both anxiety and pain. This study used a case study and the nursing process approach for people with appendicitis. The nursing process consisted of assessing the patient, analyzing nursing problems, determining priority problems, creating a nursing care plan, implementing the nursing care plan, evaluating the results of implementation, and documenting the nursing process during pre-, intra-, and post-surgery. The sample of this study was an adult male patient with appendicitis who underwent appendectomy and was hospitalized at PKU Muhammadiyah Gamping Hospital, Yogyakarta, from November 4 to 7, 2024. The patient received Benson Relaxation Therapy pre- and post-surgery. The instruments used in this study were an assessment form, the Amsterdam preoperative Anxiety and Information Scale (APAIS) to measure anxiety, and the Visual Analog Scale (VAS) to assess the pain score. The results showed a significant decrease in anxiety and pain levels after regular Benson Relaxation Therapy pre- and post-surgery. This research concluded that Benson Relaxation Therapy is effective in reducing anxiety and for pain management, especially for patients with appendectomy.